Video Animasi 2D sebagai Salah Satu Media Pembelajaran Huruf Hijaiyah dan Bahasa Arab pada TPQ Al Huda Wonodri Semarang - Bella Kartika Sari; Atika Farhana Herdajanti; Rafita Yulianing Puspiyanti; Dzauqy Shifa; Muhammad Khusni Muzzamil; Melati Oktafiyani (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2021)
Education in the religious sciences, in particular the Hijaiyah letters, is essential as a readiness to be understood by humans as the basis of life to face life in the future. The difficulty encountered is quite reasonable as the Quran uses Arabic. Learning with the Quranic system usually takes place over relatively long or even years. It is neither effective nor efficient as far as teaching and learning are concerned. As a result, with the presence of new learning media through the use of computer technology, it is expected that they will be transformed into appealing learning for children. Therefore, the authors made interactive animation videos of hijiayah letter recognition, Arabic language in daily life, writing in Arabic, and calligraphy. Those interactive animation videos for kindergarten, elementary, and junior high school-age children at TPQ Al Huda Wonodri is beneficial in the teaching and learning process to be more fun and effective so that students are no longer bored in learning and attract students to understand better how to read hijaiyah letters well and correctly.